Analisis Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Soal Fungsi Ditinjau dari Kecemasan Matematis - Hanisa Zerlina Aristiyani; Ika Victoria Nalurita (Universitas Muria Kudus, 2026)
Critical thinking skills are essential when learning mathematics. These skills help students think in a clear and logical manner. Previous research has shown that critical thinking skills can be influenced by various factors, such as anxiety about mathematics. This study aims to demonstrate how well students can think critically when solving mathematical problems involving functions, while also accounting for the students’ levels of anxiety. This study employs a qualitative descriptive method. The study involved 11th-grade students from MA Manbaul Ulum Mojopuro, comprising one student with low anxiety, one with moderate anxiety, and one with high anxiety. Data will be analyzed using three stages: data reduction, data presentation, and drawing conclusions. This study uses three methods to collect data, including a questionnaire on math anxiety, a test to measure critical thinking skills, and interviews. The results of the study indicate that students with low anxiety are able to understand the problems, plan their solutions, solve the problems correctly, and draw conclusions. Students with moderate anxiety are able to understand the problems, plan their solutions, and draw conclusions. Meanwhile, students with high anxiety are only able to understand the problems and plan their solutions